Analisis Nilai-Nilai Pendidikan Islam dalam Novel Janji Karya Tere Liye - Arsy Gusvita; Rini Rahman (Prodi Pendidikan Keagamaan Islam, 2022)
This study aims to determine the values of Islamic education in the novel Janji by Tere Liye. This research with a qualitative approach with the concept of content analysis research. Based on the problem formulation, this research focuses on what are the values of Islamic education contained in the novel Janji by Tere Liye. In collecting data, the hermeneutic analysis was used to research and examine the Janji novel, in order to obtain data to determine the values of Islamic education in the novel. The collected data are grouped and then described. The findings of the collected values are grouped into three main themes, namely: 1) the value of faith, 2) the value of worship, and 3) the value of morality. The results of this can be used as initial data for future researchers in examining different issues related to this context.